A Conceptual Framework to Measure the Freedom of Press and media Regulation in Pakistan. - Memon, Sumera; Shaikh, Muhammad Ali (Journal of Social Sciences & Humanities (1994-7046))
This article is taking a conceptual approach to test the perception of journalist and practices of journalist on freedom of press in Pakistan. Specifically, this study attempts to evaluate the perception and use of code and conducts of PEMRA (Pakistan Electronic Media and Regulatory Authority), PTA (Pakistan Telecommunication Authority) and PCP (Press Council of Pakistan). Also this study assesses the freedom and impunity against journalists during PMLN and PTI regime. A quantitative approach, in which survey questionnaires administered to 214 reporters, working in both Sindhi and Urdu media were selected through disproportionately simple random sampling. For primary data analysis SPSS software and for testing the proposed hypothesized model, Structural Equation Modelling (SEM) will be used. Findings will provide important implication to researchers, policymakers, human right organizations and media practitioners on what journalists perceive when they practice their journalistic duties on different issues while keeping the codes and conducts of PEMRA, PTI and PCP.